Prophylactic Cannabinoid Administration Blocks the Development of Paclitaxel-Induced Neuropathic Nociception during Analgesic Treatment and following Cessation of Drug Delivery. (18th April 2014) - Rahn, Elizabeth J; Deng, Liting; Thakur, Ganesh A; Vemuri, Kiran; Zvonok, Alexander M; Lai, Yvonne Y; Makriyannis, Alexandros; Hohmann, Andrea G
Background: Chemotherapeutic treatment results in chronic pain in an estimated 30–40 percent of patients. Limited and often ineffective treatments make the need for new therapeutics an urgent one. We compared the effects of prophylactic cannabinoids as a preventative strategy for suppressing development of paclitaxel-induced nociception. The mixed CB1 /CB2 agonist WIN55, 212–2 was compared with the cannabilactone CB2 -selective agonist AM1710, administered subcutaneously (s.c.), via osmotic mini pumps before, during, and after paclitaxel treatment. Pharmacological specificity was assessed using CB1 (AM251) and CB2 (AM630) antagonists. The impact of chronic drug infusion on transcriptional regulation of mRNA markers of astrocytes (GFAP), microglia (CD11b) and cannabinoid receptors (CB1, CB2 ) was assessed in lumbar spinal cords of paclitaxel and vehicle-treated rats. Results: Both WIN55, 212–2 and AM1710 blocked the development of paclitaxel-induced mechanical and cold allodynia; anti-allodynic efficacy persisted for approximately two to three weeks following cessation of drug delivery. WIN55, 212–2 (0.1 and 0.5 mg/kg/day s.c.) suppressed the development of both paclitaxel-induced mechanical and cold allodynia. WIN55, 212–2–mediated suppression of mechanical hypersensitivity was dominated by CB1 activation whereas suppression of cold allodynia was relatively insensitive to blockade by either CB1 (AM251; 3 mg/kg/day s.c.) or CB2 (AM630; 3 mg/kg/day s.c.) antagonists. AM1710 (0.032 and 3.2 mg/kg/day) suppressed development of mechanical allodynia whereas only the highest dose (3.2 mg/kg/day s.c.) suppressed cold allodynia. Anti-allodynic effects of AM1710 (3.2 mg/kg/day s.c.) were mediated by CB2 . Anti-allodynic efficacy of AM1710 outlasted that produced by chronic WIN55, 212–2 infusion. mRNA expression levels of the astrocytic marker GFAP was marginally increased by paclitaxel treatment whereas expression of the microglial marker CD11b was unchanged. Both WIN55, 212–2 (0.5 mg/kg/day s.c.) and AM1710 (3.2 mg/kg/day s.c.) increased CB1 and CB2 mRNA expression in lumbar spinal cord of paclitaxel-treated rats in a manner blocked by AM630. Conclusions and implications: Cannabinoids block development of paclitaxel-induced neuropathy and protect against neuropathic allodynia following cessation of drug delivery. Chronic treatment with both mixed CB1 /CB2 and CB2 selective cannabinoids increased mRNA expression of cannabinoid receptors (CB1, CB2 ) in a CB2 -dependent fashion. Our results support the therapeutic potential of cannabinoids for suppressing chemotherapy-induced neuropathy in humans.